Maternal and perinatal outcome in multifetal gestation - Patel, Tejal L.; Diwan, Bhargavi Ajit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Multifetal gestation is a high-risk pregnancy associated with increased maternal and fetal complications. The rate of multiple pregnancy has dramatically increased during the past decades, along with the diffusion of assisted reproduction technology (ART). The present study aims to investigate maternal and perinatal outcome in multifetal gestation. Methods: The prospective study was carried in the department of obstetrics and gynaecology, B. J. medical college, civil hospital, Ahmedabad from August 2019 to July 2020. All cases of multifetal pregnancy either admitted from antenatal clinics or from labor room as emergency cases were included in the study. Results: Out of total 7786 births during this period, 103 were twin pregnancies and 3 were triplets. The incidence was 1 in 73.5 births. Maternal complications observed were anaemia in 27.3% patients, preterm deliveries in 58% patients, PROM in 20.7% patients, hypertensive disorders of pregnancy in 13.2% patients, APH in 1.8% patients and PPH in 4.7% patients. No maternal mortality occurred. Fetal complications like gross congenital anomalies in 6.13% cases, single fetal demise in 8.49%, growth discordance in 7.53%, fetal growth restriction in 5.18% cases and 82% babies were low birth weight. Still birth rate was 8.01% and perinatal mortality rate was 12.3%. Conclusions: Early detection of high-risk cases, timely referral, frequent antenatal visits and early hospitalization with optimum obstetrics care and intensive neonatal care set up are necessary to improve maternal and perinatal outcomes.